2019
DOI: 10.1111/hae.13694
|View full text |Cite
|
Sign up to set email alerts
|

The impact of haemophilia on the social status and the health‐related quality of life in adult Lebanese persons with haemophilia

Abstract: Introduction Health‐related quality of life (HRQoL) studies are increasingly needed to prevent and improve the medical care of persons with haemophilia (PWH). Aim We assessed the impact of haemophilia on HRQoL and social status of adult Lebanese PWH compared to a reference population. Methods In this case‐control study, 60 severe and moderate PWH were compared to 112 healthy controls. Detailed socio‐demographic data and disease characteristics were collected, and HRQoL was assessed using the SF‐36 questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Despite the PWH practice less sport activities than children, either report engaging in low‐risk sports in line with the recommendation by the US National Hemophilia Foundation and the World Foundation of Hemophilia 15,16 . Furthermore, physical activity is often associated with positive effects on physical well‐being, on self‐esteem and social interactions 17 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite the PWH practice less sport activities than children, either report engaging in low‐risk sports in line with the recommendation by the US National Hemophilia Foundation and the World Foundation of Hemophilia 15,16 . Furthermore, physical activity is often associated with positive effects on physical well‐being, on self‐esteem and social interactions 17 .…”
Section: Discussionmentioning
confidence: 89%
“…Despite the PWH practice less sport activities than children, either report engaging in low-risk sports in line with the recommendation by the US National Hemophilia Foundation and the World Foundation of Hemophilia. 15,16 Furthermore, physical activity is often associated with positive effects on physical well-being, on self-esteem and social interactions. 17 Swimming was the most practiced both in adults and children, but some higher risk activities were also reported, in particular soccer (by adults and children), basketball and volleyball (by children).…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilia A has a prevalence of 17.1 cases per 100,000 males, with 6.0 cases per 100,000 males being severe Hemophilia A [14]. Despite being a rare disorder, hemophilia A poses a remarkable burden on health infrastructure [15] due to its debilitating nature [16], causing joint deformity [17] and even life-threatening bleeding [4].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not look at the socio-economic aspects of pain among participants, but studies elsewhere have indicated that this has an impact [1,35,36] . Future research should include an overall clinical assessment of PwH who experience pain, with a comparison of socioeconomic factors between those who do and do not suffer from pain in our local setting.…”
Section: Limitationsmentioning
confidence: 99%